ChemInform Abstract: Palladium‐Catalyzed α‐Arylation Reactions in Total Synthesis. Issue 10 (March 2015) - Sivanandan, Sudheesh T.; Shaji, Ashna; Ibnusaud, Ibrahim; Seechurn, Carin C. C. Johansson; Colacot, Thomas J.
Abstract Review: [recent applications of α‐arylation in total syntheses both of natural products and of active pharmaceutical ingredients; 80 refs.